2009
DOI: 10.1530/eje-09-0123
|View full text |Cite
|
Sign up to set email alerts
|

Small effect of the androgen receptor gene GGN repeat polymorphism on serum testosterone levels in healthy men

Abstract: Objective: The human androgen receptor (AR) contains a polyglutamine and a polyglycine stretch which are highly polymorphic and are coded respectively by a CAG and GGN repeat in exon 1 of the AR gene. Although the in vitro studies indicated a possible effect of the GGN repeat polymorphism on the AR gene transcription and clinical observations suggest that it might modulate the androgen action, its functional significance remains unclear. We wanted to assess whether the GGN repeat affects the serum testosterone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
3
14
1
Order By: Relevance
“…Genetic variations in the AR gene, in particulary CAG repeat polymorphisms, have been associated with disorders linked to a reduced androgen activity [27]. We have previously shown that serum T levels are positively associated with the CAG and GGN repeat length in young, middle-aged and elderly men [9], [13]. This is in contrast with the present study, in which we did not find any correlation between TT or FT and the GGN repeat length.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Genetic variations in the AR gene, in particulary CAG repeat polymorphisms, have been associated with disorders linked to a reduced androgen activity [27]. We have previously shown that serum T levels are positively associated with the CAG and GGN repeat length in young, middle-aged and elderly men [9], [13]. This is in contrast with the present study, in which we did not find any correlation between TT or FT and the GGN repeat length.…”
Section: Discussioncontrasting
confidence: 99%
“…Polymorphisms in the AR gene have been described to alter this activity. We have previously shown that diminished androgen feedback, and consequently higher serum T concentrations, are associated with the CAG repeat length, and to a lesser extend with the GGN repeat length [9], [13]. Furthermore, some single nucleotide polymorphisms (SNP) in the AR gene, resulting in an altered binding with cofactors, have been linked with the androgen insensitivity syndrome (AIS) [14][16] and could therefore affect androgen action and circulating androgen levels.…”
Section: Introductionmentioning
confidence: 99%
“…The non-significant small increase in circulating androgen levels (2.2%) could have also contributed to explaining the lower accumulation of fat mass in the GGN L group. In agreement, greater serum concentration of total testosterone and free testosterone has been reported in GNN L than in the GGN S men (32). This also concurs with the association between free testosterone and MFO, as well as between SHBG and the accumulation of trunk fat per day in this study.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the number of GGN repeats in the controls showed that GGN 23 was the only dominant allele. This was consistent with the previous study by Hsing et al (2000) based on normal urban Shanghai Chinese men, but was not consistent with another group (Bogaert et al, 2009) who found that GGN 23 and 24 alleles were dominant, suggesting that conflicting results may be attributed to varying ethnic background and sample selection criteria.…”
Section: Discussionsupporting
confidence: 85%